POLITIK HUKUM PEMBENTUKAN SATUAN TUGAS PENANGANAN COVID-19 DALAM SISTEM KETATANEGARAAN INDONESIA - Muhammad Rizal Veto; Emilda Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Currently, the world and Indonesia are also experiencing the same problem, namely experiencing a pandemic by the corona virus (Covid-19), in Indonesia itself in facing and breaking the chain of spread of the corona virus pandemic, one of them is the formation of a task force by the president. . The next thing is related to the position of BNPB in handling Covid 19. Based on Presidential Decree Number 7 of 2020 as amended by Presidential Decree Number 9 of 2020 concerning the Task Force for the Acceleration of Handling Corona Virus Disease 2019 (COVID-19), the President has formed an Acceleration Task Force.This type of research can be classified in the type of Normative legal research, which reveals legislation relating to legal theories that are the object of research. The approach taken uses a qualitative analysis approach by looking for data both in books, journals and other scientific works related to this research. The data sources used are primary and secondary legal materials.The conclusions that can be obtained from the research results are First, the Legal Politics of the Establishment of a Task Force for Handling Covid-19 in the Indonesian State Administration System. First, the aspect of service quality, in this case the accuracy of the information provided. Any information also needs to be disseminated through various media owned by the Covid-19 Task Force and the team in charge of the field. Second, in the aspect of responsiveness, tidier data collection related to the need for medical devices can be done by utilizing an integrated online application. Second, the Ideal Concept of the Covid-19 Handling Task Force Structure in the Indonesian State Administration System regarding the basis of authority and duties between BNPB and the Task Force which is not ideal because it raises questions in the community about the honorarium system to the structure whether all BNPB members become the Task Force or are there additions to the contents of the Task Force. Keywords: Task Force, Corona Virus Disease, Political Law, Indonesian State Administration.